2005
DOI: 10.1681/asn.2004060505
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic and Enhanced Sodium Restriction Results in Improved Antiproteinuric Response to RAS Blocking Agents

Abstract: P roteinuria is a major risk factor for progression to ESRD in both diabetic and nondiabetic nephropathies (1,2). Angiotensin II is a key player in the development of renal failure, either directly by promoting tissue fibrosis or indirectly through its action on glomerular hemodynamic and proteinuria (1,3-5). Therefore, inhibition of the renin-angiotensin system (RAS), through either angiotensin-converting enzyme inhibitors (ACEI) or angiotensin II receptor blockers (ARB), may have a positive impact on protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 41 publications
2
60
1
8
Order By: Relevance
“…Recently, there has been evidence to suggest that diuretics and low-salt diet may potentiate the effect of renin-aldosterone system-blocking agents (19,20). More than 70% of patients in every group were taking either a loop diuretic or thiazide diuretic, so the effect of spironolactone in reducing proteinuria is over and above that provided by concurrent use of diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been evidence to suggest that diuretics and low-salt diet may potentiate the effect of renin-aldosterone system-blocking agents (19,20). More than 70% of patients in every group were taking either a loop diuretic or thiazide diuretic, so the effect of spironolactone in reducing proteinuria is over and above that provided by concurrent use of diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a lower serum potassium level would feed back to decrease serum aldosterone levels in the absence of hypovolemia (23). Sodium depletion may also be the link between high serum aldosterone levels and low UACR and eGFR at baseline, which was previously shown (24)(25)(26). Inversely, subsequent aldosterone breakthrough was more frequent if the patient had, at baseline, the opposite profile suggestive of hypervolemia (i.e., lower serum aldosterone levels and higher SBP in multivariate analysis as well as higher UACR in univariate analysis).…”
Section: Discussionmentioning
confidence: 73%
“…sive agents) than did patients in the other investigation, whose BP was controlled with fewer than two antihypertensive agents and no RAS blockade (6). In addition, patients in the negative study excreted less sodium than those in the study that showed a positive finding (mean sodium excretion 129 to 168 versus 192 to 204 mEq/d) (5,6).…”
Section: Effect Of Dual-class Therapy On Proteinuriamentioning
confidence: 99%